2012
DOI: 10.1068/i0504
|View full text |Cite
|
Sign up to set email alerts
|

Awareness of the Light Field: The Case of Deformation

Abstract: Human observers group local shading patterns into global super-patterns that appear to be illuminated in some unitary fashion. Many years ago, this was noticed for the case of uniform, unidirectional illumination. Recently, we found that it also applies to convergent and divergent illumination flows, but that human observers are blind to rotational light flow patterns (in the sense of being unable to group the local shading patterns). We now report that human observers are also blind to deformation patterns. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 31 publications
2
21
0
Order By: Relevance
“…The results of Experiments 1 and 2 are broadly consistent with the findings of van Doorn et al (2011Doorn et al ( , 2012. They found that observers perceived simulated bump patterns in accordance with the simulated illumination field when the lighting conditions were typical of real-world scenes (i.e., uniform or divergent), but not when lighting direction varied from place to place either too rapidly (their ''random'' condition) or in a physically implausible way (e.g., their ''circular'' conditions).…”
Section: Resultssupporting
confidence: 85%
See 1 more Smart Citation
“…The results of Experiments 1 and 2 are broadly consistent with the findings of van Doorn et al (2011Doorn et al ( , 2012. They found that observers perceived simulated bump patterns in accordance with the simulated illumination field when the lighting conditions were typical of real-world scenes (i.e., uniform or divergent), but not when lighting direction varied from place to place either too rapidly (their ''random'' condition) or in a physically implausible way (e.g., their ''circular'' conditions).…”
Section: Resultssupporting
confidence: 85%
“…Morgenstern, Murray, and Harris (2011) found that observers use lighting cues on one object to infer shape from shading on a separate object that is several degrees of visual angle away, reflecting a preference for smooth changes in lighting. van Doorn, Koenderink, and Wagemans (2011) and van Doorn, Koenderink, Todd, and Wagemans (2012) found that observers are strongly biased to perceive lighting conditions that are either collimated, like light on a sunny day, or diverging, like light radiating outwards from a candle. Observers were unable to see shaded images as illuminated by other, less common lighting patterns, such as cyclical light fields where lighting directions form a closed loop.…”
Section: Introductionmentioning
confidence: 99%
“…A case with negative rank correlation is surely spurious, and we would consider ignoring this observer as 'outlier'. We know from previous studies that a fair fraction of the general population fails to use the 'shading cue' to some degree, or even totally (van Doorn et al, 2012). Such observers report that they experience the conventional shading stimulus as a flat gradient of tone.…”
Section: Resultsmentioning
confidence: 99%
“…A common wisdom in vision science is that 'equiluminant' chromatic modulations prevent depth and shape cues to be effective (Livingstone and Hubel, 1987). However, other studies have not invariably found this (Cavanagh, 2009;Cavanagh et al, 1992;van Doorn et al, 2005). This is at least partly due to the operational definition of equiluminance.…”
Section: Rationale Of the Studymentioning
confidence: 99%
“…In the latter case one may discuss the nature of their awareness with the observers. We have met with a variety of interesting cases, like inability to become visually aware—as different from reasoning out—of concavities (van Doorn, Koenderink, Todd, & Wagemans, 2012). …”
Section: Discussionmentioning
confidence: 99%